PENGARUH LATIHAN TEKNIK ALEXANDER TERHADAP TINGKAT NYERI PUNGGUNG BAWAH PADA IBU HAMIL TRIMESTER 3 - Endah Dwi Cahyani, (2023)
Back pain in pregnant women is pain located in the lower back caused by the increase in uterine size which results in changes in the body's center of gravity and then increases pressure on the spine and the effects of pregnancy hormones such as progesterone and relaxin. This study aims to determine the effect of giving alexander technique exercises to pregnant women in 3rd trimester. This research design is quasy experimental with a pretest posttest research plan nonequivalent control group design. The sampling technique of this study was total sampling with sample characteristics of 3rd-trimester pregnant women who experienced low back pain totaling 44 people. Respondents were divided into intervention groups and control groups. In the intervention group, 8 Alexander technique training sessions were carried out for 1 month with 2 sessions per week, while in the control group no intervention was carried out. The instrument used in this study was a visual analog scale. From this study, the results of the paired T test pre-post-intervention and the results of the independent T test P value <0.05 which can be concluded that there is a significant effect of Alexander technique training on the level of low back pain in pregnant women in 3rd trimester. From this study, it is recommended that this exercise can be applied by pregnant women in the 3rd trimester to reduce complaints of low back pain